Volunteering and Sustainable Development - Lapidis, Konstantinos (HAPSc Policy Briefs Series, 2020)
Volunteering as an action brings all the necessary elements of social activation of the individual on a voluntary basis, which gives a particular dynamic to voluntary organizations as part of civil society. Voluntary organizations are actors of ideas and potential partners of the state in pursuing their objectives. On this basis, it is very important to develop a dialog among the local and central authorities with these organizations, with a view to making them an active part in policy-making and a tool to awaken citizens about development issues and beyond. Volunteering as a tool can lead to a fundamental change in citizens’ attitudes and bring about a shift towards sustainable solutions, always through dialog and with the assistance of the state.